The Medieval Cornish Bible: More Evidence. (1st May 2008) - Grigg, Erik
This article seeks to continue the debate surrounding the existence of a medieval Cornish Bible, arguing that previous contributions have missed some important evidence and made some erroneous assumptions. Various commentators have argued that that the failure to translate the Bible (and the Prayer Book) into Cornish accelerated the replacement of the language by English, in the process destroying the last vestiges of its status and esteem. When a language is utilized as a vehicle for the 'Word of God' it gains authority, something that Cornish appeared to lack by the sixteenth and seventeenth centuries when the local gentry saw it as merely the tongue of the poor and powerless. In the eighteenth century, as part of a 'revivalist project to restore the language, Cornish scholars such as William Gwavas (1676-1741) and John Keigwin (1641-1710) advocated the production of a Bible in Cornish; in 2002, as part of the contemporary revivalist movement, the New Testament appeared in Unified Cornish Revised, to be followed two years later by a Common Cornish version. These attempts to produce a Cornish Bible demonstrate that even in today's secular age a Bible translation gives credibility to a language. And, as the Bible is a large and complex book, such translation inevitably stimulates academic study of the language in question.